Geokimia (XRF) Batuan Andesit Daerah Putiana Dan Sekitarnya, Kecamatan Anggrek, Kabupaten Gorontalo Utara - Hemeto, Fasya Ramadhan; Arifin, Yayu Indriati; Hutagalung, Ronal (Journal of Applied Geoscience and Engineering, 2025)
This research was conducted in Putiana village and its surrounding area, Anggrek District, North Gorontalo Regency. The geographical position of this area is at 122°47'09.9'' - 122°48'31.9'' East Longitude and 0°48'43.3'' - 0°50'00.3â€ North Latitude (WGS84 Zone 51N) with a study area of 6 km². The research was conducted with the aim of knowing the geochemistry of andesite rocks and the tectonic order that occurred in the research area. The method used in this research is geological mapping which aims to determine the geological conditions and X-ray fluorescence (XRF) geochemical analysis to determine the chemical content of rocks. The results showed that the stratigraphy of the research area when sorted from old to young includes andesite porphyry units, andesite units, and alluvial sediment units. Based on geochemical analysis, it is known that the magma type of the andesite rock series of the research area is tholeiitic and includes basalt rock types. The magma origin is Island Arc Tholeiitic, with the tectonic setting of the research area occurring in the orogenous zone/subduction zone.